Auditory brainstem implantation. - Wackym PA; Runge-Samuelson CL; Firszt JB (Operative Techniques in Otolaryngology - Head & Neck Surgery, 2005)
Auditory brainstem implants are auditory prostheses designed to treat deafness in patients with neurofibromatosis type II (NF2). The auditory brainstem implant protocol used by our group includes microsurgical and endoscopic placement of the electrode pad, electrophysiologic testing in the operating room to ensure optimal placement, and psychophysical/behavioral testing for appropriate stimulation and longitudinal follow-up of the patient. With this protocol we have achieved excellent outcomes relative to those achieved by other centers. Our methods are described herein. Copyright © 2005 by Elsevier Science (USA).